2021
DOI: 10.2196/31374
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Video Consultation Services at Pace and Scale in Scotland During the COVID-19 Pandemic: National Mixed Methods Case Study

Abstract: Background Scotland—a country of 5.5 million people—has a rugged geography with many outlying islands, creating access challenges for many citizens. The government has long sought to mitigate these through a range of measures including an ambitious technology-enabled care program. A strategy to develop a nationwide video consultation service began in 2017. Our mixed methods evaluation was commissioned in mid-2019 and extended to cover the pandemic response in 2020. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 64 publications
3
102
0
1
Order By: Relevance
“…Findings from our research suggest that this policy narrative, and the mismatch with frontline experiences, has continued during the pandemic: what decision makers viewed as an opportunity to scale up video consulting appeared to be at odds with what many in primary care viewed as disruption in terms of the work involved in "rapidly shifting existing organizational practices to new digital spaces" [(104), p. 4]. This builds on earlier work on technological innovation in health care and the challenges of routinizing new technologies in everyday practice [e.g., (48,74,123)].…”
Section: What Our Findings Add To Existing Literaturementioning
confidence: 79%
See 2 more Smart Citations
“…Findings from our research suggest that this policy narrative, and the mismatch with frontline experiences, has continued during the pandemic: what decision makers viewed as an opportunity to scale up video consulting appeared to be at odds with what many in primary care viewed as disruption in terms of the work involved in "rapidly shifting existing organizational practices to new digital spaces" [(104), p. 4]. This builds on earlier work on technological innovation in health care and the challenges of routinizing new technologies in everyday practice [e.g., (48,74,123)].…”
Section: What Our Findings Add To Existing Literaturementioning
confidence: 79%
“…This work involved quantitative and qualitative data collection and the production of narrative case studies to illustrate the successes, failures and partial successes of efforts to use this technology in different settings and services. The Scottish example is interesting because much work was put into building a national infrastructure and branding for the video consultation model (48). We were then commissioned by the Scottish Government to extend this work and document how things changed during the COVID-19 response.…”
Section: Study Design and Use Of Existing Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may reflect differences in clinical need and the ability to engage in remote consultations as well as their perceived effectiveness for a given problem. Such individuals may have greater overall debility and fewer resources to effectively access remote delivered healthcare, as illustrated by Wherton et al [ 40 ] in a study of video consultations pre and during the COVID-19 pandemic in Scotland. They found that comorbidities and pre-existing conditions, along with a general level of debility influenced people’s ability to use video technology.…”
Section: Discussionmentioning
confidence: 99%
“…This insightful paper by Wherton et al [ 1 ] suggests groundwork before the pandemic allowed health care services to rapidly extend the use of video consultations across Scotland. As a general practitioner and digital champion, working in a deprived area in a city in Scotland, I agree but strongly believe that front-line staff is fundamental to further increase use.…”
mentioning
confidence: 99%